The Development of Professional Motivation of the Activity Subject under Specific Conditions - Osodlo, Vasyl I.; Perepeliuk, Tetiana D.; Kovalchuk, Oleksandr P.; Osadchenko, Inna I.; Vintoniak, Viktoriia F. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The study aims to clarify the most crucial interconnections of professional motivation with the features of this activity, its dependence on professional motivation and the personal traits of officers. Background: The article presents the results of motivational research of the professional activity of officers. The received empirical data define the differences in visibility of professional motives and aims of activity, means and conditions of their implementation depending on the stage of professional development of the tested. Method: The main research methods are: the study of literature on the research problem; the diagnosis of the visibility of the most prominent motives of the tested professional goals and the aims of their achievement have been carried out with the aid of the developed survey the core of which is formed by the requirements to reflect in its structure the holistic psychological, professional, social and other peculiarities of the MPA of officers. Results: There's been research conducted on the interconnection of professional activity with personal traits and features, which has allowed to determine the peculiarities of personal determinacy of separate motivational components. As a result of this research, it has been established, that the demonstration of professional motives and aims of activity in the process of personal development depends on personal qualities. Conclusion: At the first stage the more significant qualities are considered to be openness to receive new experience, initiative in terms of social contacts, high level of neuroticism, internality in the sphere of achievements; at the second stage – decency, the inclination to approve, internality in terms of interpersonal communication, at the third stage – emotional sustainability, the inclination to approve, internality in terms of life perception, internality in terms of family.